The influence of methodological variables on the push‐out resistance to dislodgement of root filling materials: a meta‐regression analysis. (22nd September 2015) - Collares, F. M.; Portella, F. F.; Rodrigues, S. B.; Celeste, R. K.; Leitune, V. C. B.; Samuel, S. M. W.
Abstract: The aim of this systematic review was to evaluate the influence of several methodological variables on the push‐out resistance to dislodgment of root filling materials by a meta‐regression analysis of the literature. A systematic review was performed by searching the PubMed database using the terms 'push‐out' and 'pushout'. Laboratory studies published before March 2015 were included. Two reviewers extracted data regarding country of origin, year of publication, tooth type, smear layer removal, root canal sealer, core material, obturation technique, sample storage, tooth portion, test machine load velocity and slice thickness. Pooled mean resistance to dislodgement of all groups from the included studies was used in a linear meta‐regression of random effects (α = 0.05). Of the 850 identified studies, 53 met the inclusion criteria. A meta‐regression of the 341 groups extracted from these articles was performed to analyse the influence of each variable on resistance to dislodgement (in MPa). The sealer, core material, obturation technique, slice thickness, storage time, load velocity and tooth portion significantly influence the results ( P  < 0.05). Irrigant solution and smear layer removal did not influence the resistance to dislodgement of the root filling materials ( P  > 0.05). Methodological variables such as sealer, core material, root filling technique, tooth type, tooth portion, slice thickness, storage time and load velocity influenced the resistance to dislodgment. The inclusion and standardization of all related variables could lead to a more comparable and reproducible analysis of the resistance to dislodgment of the root canal sealers.